The Rose Society : a Young Elites Novel - Lu, Marie 1984- (New York, NY : G.P. Putnam's Sons, 2015)
Known and feared as the White Wolf, Adelina Amouteru and her sister flee Kenettra to find other Young Elites in the hopes of building her own army of allies. But as Adelina's powers (fed only by fear and hate) start to grow beyond her control, she also distrusts her newfound Elite friends. Teren Santoro, leader of the Inquisition, wants her dead. And her former friends, Raffaele and the Dagger Society, want to stop her thirst for vengeance. Adelina struggles to cling to the good within her. But how can someone be good, when her very existence depends on darkness?
Keywords: Paranormal fiction; Ability -- Juvenile fiction; Adventure stories; Secret societies -- Juvenile fiction; Revenge -- Juvenile fiction; Fantasy -- Juvenile fiction; Supernatural -- Fiction; Ability -- Fiction; Adventure and adventurers -- Fiction; Secret societies -- Fiction; Revenge -- Fiction; Fantasy